A high performance and high thermal conductivity composite phase change material and its preparation process and application
By using foam graphite composite PCM particles and ester-based multi-walled carbon nanotubes in graphite composite phase change materials, and adding polyurethane, the problems of thermal inhomogeneous material and phase separation are solved, and the combination of high thermal conductivity and fluidity is achieved.
Patent Information
- Application Number
- CN202510116976.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The existing graphite composite phase change materials are uneven in thermal absorption and energy storage, and have high hardness and no fluidity, which limits their application in many scenarios. At the same time, phase separation is prone to occur during thermal circulation.
Foam graphite composite PCM particles and ester-based multi-wall carbon nanotubes are used as high thermal conductivity fillers, and the addition of polyurethane is used to form a temporary network structure to improve fluidity and thermal conductivity and reduce the risk of phase separation.
The thermal conductivity of the material is significantly improved to more than 15 times that of the pure phase change material, while maintaining a high latent heat of phase change and a certain fluidity, extending the stability of the material's recycling.
Smart Images

Figure CN119552637B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change energy storage materials, and in particular to a high-performance and high-thermal-conductivity composite phase change material and a preparation process and application thereof. Background Art
[0002] Phase change materials (PCM) absorb or release a large amount of heat energy during phase change to achieve energy storage and utilization, and are one of the important means to solve energy problems. Especially in the context of increasing global energy shortages and the rapid development of the new energy industry, phase change energy storage has become a very hot frontier science in energy conservation and material science in recent years. Common phase change materials include: paraffin, long-chain acids, alcohols, esters, etc. They are abundant in sources, low in price, and have excellent performance. They are popular for their non-toxic, eco-friendly bio-based properties, low vapor pressure during phase change, low degree of supercooling, and good compatibility with various materials. However, at the same time, they also have the disadvantages of low thermal conductivity, large solid-liquid volume difference during phase change, and easy leakage of the liquid phase.
[0003] By compounding phase change materials with graphite with large porosity and a three-dimensional interconnected network structure, the thermal conductivity of the material can be improved while reducing liquid phase leakage. However, in the process of heat absorption and energy storage of graphite composite phase change materials, its stable solid form hinders the uniform transfer of heat, and the high hardness and lack of fluidity of the material also hinder the multi-scenario application of graphite composite phase change materials. The fluidity and phase change enthalpy of the phase change system can be improved by compounding PCM with graphite composite phase change materials. However, as the proportion of PCM increases, the thermal conductivity of the system will also decrease accordingly. At the same time, during the thermal cycle use of the PCM-graphite compound system, phase separation of liquid PCM and graphite composite phase change materials is prone to occur, which imposes certain restrictions on its scope of application.
[0004] Wang Jing et al. (Heat Treatment Technology and Equipment, 2016, 37(05):1-4) used high-density polyethylene to perform secondary packaging on graphite wax composite materials by melt blending, and the thermal conductivity increased from 0.5 W / m·K to 1.2 W / m·K, but the latent heat decreased from 230 J / g to 159 J / g. Its solid form also limits the application of the material in some special scenarios. The thermal conductivity of the phase change material prepared by Chinese patents CN115612462A, CN113621349A and Fu Hao et al. (Polymer Materials Science and Engineering, 2024, 40(05):144-153) is less than 1 W / m·K; the thermal conductivity of the flexible thermally conductive phase change material prepared by Chinese patent CN113652204A reaches 3 W / m·K, but it remains in a solid form and lacks fluidity, which has caused certain limitations for the application of some scenarios.
[0005] Based on this, the present invention provides a high-performance and high-thermal-conductivity composite phase change material and its preparation process and application. Summary of the invention
[0006] The purpose of the present invention is to provide a high-performance and high-thermal conductivity composite phase change material and its preparation process and application, to optimize the phase separation problem of solid-liquid composite phase change materials with graphite as the main heat-maintaining material in the related technology, and to increase the thermal conductivity to more than 15 times that of pure phase change materials while having a certain fluidity and reducing the latent heat of phase change very little.
[0007] In a first aspect, the present invention provides a high-performance and high-thermal-conductivity composite phase change material, comprising the following materials in parts by weight: 5 to 50 parts of PCM, 70 to 150 parts of foamed graphite composite PCM particles, 0.01 to 1 part of a nucleating agent, 1 to 5 parts of a high-thermal-conductivity filler, and 5 to 30 parts of polyurethane.
[0008] Furthermore, the foamed graphite composite PCM particles include 1 to 10 parts of foamed graphite and 10 to 140 parts of PCM.
[0009] Furthermore, the polyurethane is a polyether polyurethane gel with a Shore C hardness of 0-50 Shore C hardness.
[0010] Furthermore, the PCM includes fatty acid esters such as methyl hexadecanoate, methyl octadecanoate, ethylene glycol distearate, and one or more of 1-dodecanol and 1-tetradecanol.
[0011] Furthermore, the carbon content of the foamed graphite is 99%, and its density includes any value between 0.03 and 0.3 g / cm³.
[0012] Furthermore, the nucleating agent includes one or more of TiO2, ZnO, Al2O3, SiC, and AgI.
[0013] Furthermore, the high thermal conductivity filler is esterified multi-walled carbon nanotubes.
[0014] Furthermore, the preparation process of the esterified multi-walled carbon nanotubes includes: adding carboxylated carbon nanotubes (MWCNTs-COOH) to N,N-dimethylformamide (DMF), ultrasonically dispersing for 30 minutes, slowly adding phosphorus trichloride (PCl3), reacting at 70°C for 14 hours, vacuum filtering the feed liquid, washing the filter cake with DMF for 3-5 times, removing unreacted PCl3, adding the filter cake to organic alcohol and triethylamine (TEA), heating to 50°C, magnetically stirring for 24 hours, cooling and filtering, washing the filter cake with deionized water for 3-5 times, and drying to constant weight.
[0015] In a second aspect, the present invention provides a process for preparing a high performance and high thermal conductivity composite phase change material, the steps comprising:
[0016] S1. Preheating and melting: Heat the PCM raw material to 50~150℃ to ensure full melting;
[0017] S2. Adding nucleating agent: When the temperature drops to 40-80°C, add the nucleating agent and stir at a speed of 350-500 r / min for 1-2 hours to ensure that the nucleating agent is evenly distributed in the liquid PCM to obtain a liquid feed;
[0018] S3. Vacuum impregnation: The foamed graphite sheet is mixed with the liquid, and the vacuum degree is -0.1Mpa, the heating temperature is 40~80 ℃, and the impregnation is 3~15 hours;
[0019] S4 cooling and crushing: The impregnated graphite foam plate is removed, cooled and dried, crushed, sieved through 20 mesh to obtain a graphite composite phase change powder;
[0020] S5. Retracting and adding: Adding the high thermal conductivity filler, the graphite composite phase change powder obtained in step S4, and the polyurethane A liquid to the remaining portion of the liquid in step S3, maintaining the temperature at 40~80°C, the speed at 350~500r / min, stirring for 2~3 hours to ensure that the components are evenly mixed;
[0021] S6. At 40-80° C., mix the mixed material solution in step S5 with the polyurethane B solution to obtain a high-performance and high-thermal-conductivity graphite composite phase change material.
[0022] Furthermore, the polyurethane A liquid includes 2,2-dihydroxymethylbutyric acid, α-acetyl-γ-butyrolactone and guanidine carbonate, and the polyurethane B liquid includes a mixed prepolymer of polytetramethylene glycol, 4,4'-diisocyanate dicyclomethane, isophorone diisocyanate and dibutyltin dilaurate.
[0023] In a third aspect, the high performance and high thermal conductivity composite phase change material of the present invention is applied in phase change energy storage materials.
[0024] The beneficial effects of the present invention are:
[0025] The present invention reduces the polarity of carbon nanotubes and weakens the capillary effect by esterifying multi-walled carbon nanotubes. The dispersion force between the carbon nanotubes containing ester groups and the phase change material molecules makes them have good dispersibility and wettability in the system. The present invention uses esterified multi-walled carbon nanotubes (MWCTNs) as high thermal conductivity fillers. MWCTNs build a heat transfer bridge for the dispersed graphite / PCM particles in the system, reducing the interface thermal resistance of polyurethane-PCM-graphite / PCM, and increasing the thermal conductivity of the system to more than 15 times that of pure phase change materials.
[0026] The present invention adds a certain amount of nucleating agent into the composite system, which can promote PCM nucleation, accelerate the crystallization rate of the system, and improve the recycling efficiency of the system; polyurethane is introduced to increase the viscosity of the fluid, effectively alleviate the occurrence of phase separation of the system, and improve the cyclic stability of the system; the fluidity and softness of the system can be adjusted by adding polyurethane in different proportions.
[0027] The invention has a simple process, relatively low cost, and a simple and efficient production method. The product prepared in the invention has many excellent properties such as certain fluidity, high thermal conductivity, high latent heat, etc., so that it has a very broad application prospect in the fields of aerospace, shipbuilding, military industry, medical treatment, tableware, household daily necessities, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a process flow chart of the present invention;
[0029] Figure 2 It is a schematic diagram of the structure of the composite phase change material of the present invention;
[0030] Figure 3 This is a comparison diagram of phase separation observations after 1500 thermal cycles of Examples 1-3 and Comparative Examples 1-5. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the process of preparing the phase change material, the present invention controls the phase change temperature by changing the type of PCM selected; adjusts the thermal conductivity of the system by changing the ratio of foamed graphite to MWCTNs; and adjusts the phase change latent heat, softness and fluidity of the system by changing the ratio of PCM, graphite and polyurethane. In the above manner, the preparation of the phase change system with different parameter requirements in different scenarios can be met.
[0033] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. Example 1
[0034] like Figure 1 As shown, this embodiment provides a high-performance and high-thermal-conductivity composite phase change material, which is prepared by the following steps, calculated by weight:
[0035] S1. Preheating and melting: preheat the heating stirring furnace, heat 118 parts of methyl hexadecanoate to 60 ° C to ensure that the raw materials are fully melted;
[0036] S2. Adding nucleating agent: The temperature of the heating stirring furnace was lowered to 40 ° C, 0.02 parts of α-Al2O3 were added, the stirring paddle was turned on, and the stirring speed was 400r / min for 2 hours to ensure that the nucleating agent was evenly distributed in the liquid PCM to obtain the liquid;
[0037] S3. Vacuum impregnation: 9 parts of 0.055g / cc graphite foam plates were placed in a vacuum heating kettle, and the liquid in step S2 was sucked into the vacuum heating kettle by an oil pump, at a vacuum degree of -0.1Mpa, a heating temperature of 40 ° C, and impregnated for 4.5 hours;
[0038] S4 cooling and crushing: The impregnated graphite foam plate is removed, cooled and dried, and crushed into a grinder, sieved through 20 mesh to obtain a graphite composite phase change powder for standby;
[0039] S5. Re-drawing and feeding: withdraw 28 parts of the remaining methyl hexadecanoate in the vacuum heating kettle in step S3 into a heated stirring furnace, and sequentially add 1.5 parts of ester-modified MWCTNs, 99 parts of the graphite composite phase change powder obtained in step S4, and 6 parts of polyurethane A liquid; maintain the temperature at 40 ° C, the speed at 350 r / min, and stir for 3 hours to ensure that the components are evenly mixed;
[0040] S6. At 40°C, mix the mixed liquid in step S5 with 3 parts of polyurethane B liquid to obtain a high-performance and high-thermal-conductivity graphite composite phase change material with a phase change temperature of 28°C, a phase change latent heat of 212 J / g, and a thermal conductivity of 5.1 W / mK. Example 2
[0041] This embodiment provides a high-performance and high-thermal-conductivity composite phase change material, which is prepared by the following steps, calculated by weight:
[0042] S1. Preheating and melting: preheat the heating stirring furnace, heat 118 parts of 1-tetradecanol to 70 ° C, and ensure that the raw materials are fully melted;
[0043] S2. Add nucleating agent: lower the temperature of the heating stirring furnace to 50°C, add 0.02 parts of α-Al2O3, turn on the stirring paddle, stir at 400r / min for 2 hours, and ensure that the nucleating agent is evenly distributed in the liquid PCM to obtain a slurry;
[0044] S3. Vacuum impregnation: 9 parts of 0.055g / cc graphite foam plates were placed in a vacuum heating kettle, and the liquid in step S2 was sucked into the vacuum heating kettle by an oil pump, at a vacuum degree of -0.1Mpa, a heating temperature of 50 ° C, and impregnated for 4.5 hours;
[0045] S4. Cooling and crushing: The impregnated foamed graphite plate is taken out, cooled and dried, and then put into a crusher for crushing. The graphite composite phase change powder is sieved through 20 mesh for standby use.
[0046] S5. Re-drawing and feeding: withdraw 28 parts of the remaining 1-tetradecanol in the vacuum heating kettle in step S3 into a heated stirring furnace, and sequentially add 1.5 parts of ester-modified MWCTNs, 99 parts of the graphite composite phase change powder obtained in step S4, and 6 parts of polyurethane A liquid; maintain the temperature at 50°C, the speed at 350r / min, and stir for 3 hours to ensure that the components are evenly mixed;
[0047] S6. At 50°C, mix the mixed material in step S5 with 3 parts of polyurethane B liquid to obtain a high-performance and high-thermal-conductivity graphite composite phase change material with a phase change temperature of 44°C, a phase change latent heat of 202 J / g, and a thermal conductivity of 4.9 W / mK. Example 3
[0048] This embodiment provides a high-performance and high-thermal-conductivity composite phase change material, which is prepared by the following steps, calculated by weight:
[0049] S1. Preheating and melting: preheat the heating stirring furnace, heat 118 parts of ethylene glycol distearate to 80 ° C, and ensure that the raw materials are fully melted;
[0050] S2. Adding nucleating agent: The temperature of the heating stirring furnace was lowered to 70 ° C, 0.02 parts of α-Al2O3 were added, the stirring paddle was turned on, and the stirring speed was 400r / min for 2 hours to ensure that the nucleating agent was evenly distributed in the liquid PCM to obtain the liquid;
[0051] S3. Vacuum impregnation: Place 9 portions of 0.055g / cc graphite foam plates into a vacuum heating kettle, and suck the liquid in step S2 into the vacuum heating kettle through an oil pump. Impregnate for 4.5 hours at a vacuum degree of -0.1Mpa and a heating temperature of 70°C;
[0052] S4. Cooling and crushing: The impregnated foamed graphite plate is taken out, cooled and dried, and then put into a crusher for crushing. The graphite composite phase change powder is sieved through 20 mesh for standby use.
[0053] S5. Re-drawing and feeding: withdraw 28 parts of the remaining ethylene glycol distearate in the vacuum heating kettle in step S3 into a heated stirring furnace, and sequentially add 1.5 parts of ester-modified MWCTNs, 99 parts of the graphite composite phase change powder obtained in step S4, and 6 parts of polyurethane A liquid; maintain the temperature at 70 ° C, the speed at 450 r / min, and stir for 3 hours to ensure that the components are evenly mixed;
[0054] S6. At 70°C, mix the mixed liquid in step S5 with 3 parts of polyurethane B liquid to obtain a high-performance and high-thermal-conductivity graphite composite phase change material with a phase change temperature of 65°C, a phase change latent heat of 206 J / g, and a thermal conductivity of 5.1 W / mK.
[0055] Comparative Example 1
[0056] This comparative example provides a high-performance and high-thermal-conductivity composite phase change material, which is prepared by the following steps, calculated by weight:
[0057] S1. Preheating and melting: preheat the heating stirring furnace, heat 118 parts of methyl hexadecanoate to 60 ° C to ensure that the raw materials are fully melted;
[0058] S2. Adding nucleating agent: The temperature of the heating stirring furnace was lowered to 40 ° C, 0.02 parts of α-Al2O3 were added, the stirring paddle was turned on, and the stirring speed was 400r / min for 2 hours to ensure that the nucleating agent was evenly distributed in the liquid PCM to obtain the liquid;
[0059] S3 vacuum impregnation: 9 parts of 0.055g / cc graphite foam plate was placed in a vacuum heating kettle, the liquid in step S2 was sucked into the vacuum heating kettle by an oil pump; the vacuum degree was -0.1Mpa, the heating temperature was 40 ℃, and the impregnation was 4.5 hours;
[0060] S4 cooling and crushing: The impregnated graphite foam plate is removed, cooled and dried, and crushed into a grinder, sieved through 20 mesh to obtain a graphite composite phase change powder for standby;
[0061] S5. Re-drawing and feeding: 28 parts of the remaining methyl hexadecanoate in the vacuum heating kettle in step S3 were withdrawn into a heated stirring furnace, and 1.5 parts of modified MWCTNs, 99 parts of the graphite composite phase change powder obtained in step S4, and 10 parts of polyurethane A liquid were added in sequence; the temperature was maintained at 40 ° C, the speed was 350r / min, and stirred for 3 hours to ensure that the components were evenly mixed;
[0062] S6. At 40°C, mix the mixed liquid in step S5 with 5 parts of polyurethane B liquid to obtain.
[0063] Comparative Example 2
[0064] This comparative example provides a high-performance and high-thermal-conductivity composite phase change material, which is prepared by the following steps, calculated by weight:
[0065] S1. Preheating and melting: preheat the heating stirring furnace, heat 118 parts of methyl hexadecanoate to 60 ° C to ensure that the raw materials are fully melted;
[0066] S2. Adding nucleating agent: The temperature of the heating stirring furnace was lowered to 40 ° C, 0.02 parts of α-Al2O3 were added, the stirring paddle was turned on, and the stirring speed was 400r / min for 2 hours to ensure that the nucleating agent was evenly distributed in the liquid PCM to obtain the liquid;
[0067] S3 vacuum impregnation: 9 parts of 0.055g / cc graphite foam plate was placed in a vacuum heating kettle, the liquid in step S2 was sucked into the vacuum heating kettle by an oil pump; the vacuum degree was -0.1Mpa, the heating temperature was 40 ℃, and the impregnation was 4.5 hours;
[0068] S4 cooling and crushing: The impregnated graphite foam plate is removed, cooled and dried, and crushed into a grinder, sieved through 20 mesh to obtain a graphite composite phase change powder for standby;
[0069] S5. Re-drawing and feeding: 28 parts of the remaining methyl hexadecanoate in the vacuum heating kettle in step S3 were withdrawn into a heated stirring furnace, and 1.5 parts of modified MWCTNs, 99 parts of the graphite composite phase change powder obtained in step S4, and 4 parts of polyurethane A liquid were added successively; the temperature was maintained at 40 ° C, the speed was 350 r / min, and stirred for 3 hours to ensure that the components were evenly mixed;
[0070] S6. At 40°C, mix the mixed liquid in step S5 with 2 parts of polyurethane B liquid to obtain.
[0071] Comparative Example 3
[0072] This comparative example provides a high-performance and high-thermal-conductivity composite phase change material, which is prepared by the following steps, calculated by weight:
[0073] S1. Preheating and melting: preheat the heating stirring furnace, heat 118 parts of methyl hexadecanoate to 60 ° C to ensure that the raw materials are fully melted;
[0074] S2. Adding nucleating agent: The temperature of the heating stirring furnace was lowered to 40 ° C, 0.02 parts of α-Al2O3 were added, the stirring paddle was turned on, and the stirring speed was 400r / min for 2 hours to ensure that the nucleating agent was evenly distributed in the liquid PCM to obtain the liquid;
[0075] S3 vacuum impregnation: 9 parts of 0.055g / cc graphite foam plate was placed in a vacuum heating kettle, the liquid in step S2 was sucked into the vacuum heating kettle by an oil pump; the vacuum degree was -0.1Mpa, the heating temperature was 40 ℃, and the impregnation was 4.5 hours;
[0076] S4 cooling and crushing: The impregnated graphite foam plate is removed, cooled and dried, and crushed into a grinder, sieved through 20 mesh to obtain a graphite composite phase change powder for standby;
[0077] S5. Recycle and add materials: 28 parts of the remaining methyl hexadecanoate in the vacuum heating kettle described in step S3 are withdrawn into a heated stirring furnace, and 1.5 parts of modified MWCTNs and 99 parts of the graphite composite phase change powder obtained in step S4 are added in sequence; the temperature is maintained at 40°C and the speed is 350r / min, and stirred for 3 hours to ensure that the components are evenly mixed.
[0078] Comparative Example 4
[0079] This comparative example provides a high-performance and high-thermal-conductivity composite phase change material, which is prepared by the following steps, calculated by weight:
[0080] S1. Preheating and melting: preheat the heating stirring furnace, heat 118 parts of methyl hexadecanoate to 50 ° C to ensure that the raw materials are fully melted;
[0081] S2. Adding nucleating agent: The temperature of the heating stirring furnace was lowered to 40 ° C, 0.02 parts of α-Al2O3 were added, the stirring paddle was turned on, and the stirring speed was 400r / min for 2 hours to ensure that the nucleating agent was evenly distributed in the liquid PCM to obtain the liquid;
[0082] S3 vacuum impregnation: 9 parts of 0.055g / cc graphite foam plate was placed in a vacuum heating kettle, the liquid in step S2 was sucked into the vacuum heating kettle by an oil pump; the vacuum degree was -0.1Mpa, the heating temperature was 40 ℃, and the impregnation was 4.5 hours;
[0083] S4 cooling and crushing: The impregnated graphite foam plate is removed, cooled and dried, and crushed into a grinder, sieved through 20 mesh to obtain a graphite composite phase change powder for standby;
[0084] S5. Re-drawing and feeding: 28 parts of the remaining methyl hexadecanoate in the vacuum heating kettle in step S3 were withdrawn into a heated stirring furnace, and 3 parts of modified MWCTNs, 99 parts of the graphite composite phase change powder obtained in step S4, and 6 parts of polyurethane A liquid were added in sequence; the temperature was maintained at 40 ° C, the speed was 350r / min, and stirred for 3 hours to ensure that the components were evenly mixed;
[0085] S6. At 40°C, mix the mixed liquid in step S5 with 3 parts of polyurethane B liquid to obtain.
[0086] Comparative Example 5
[0087] This comparative example provides a high-performance and high-thermal-conductivity composite phase change material, which is prepared by the following steps, calculated by weight:
[0088] S1. Preheating and melting: preheat the heating stirring furnace, heat 118 parts of methyl hexadecanoate to 50 ° C to ensure that the raw materials are fully melted;
[0089] S2. Adding nucleating agent: The temperature of the heating stirring furnace was lowered to 40 ° C, 0.02 parts of α-Al2O3 were added, the stirring paddle was turned on, and the stirring speed was 400r / min for 2 hours to ensure that the nucleating agent was evenly distributed in the liquid PCM to obtain the liquid;
[0090] S3 vacuum impregnation: 9 parts of 0.055g / cc graphite foam plate was placed in a vacuum heating kettle, the liquid in step S2 was sucked into the vacuum heating kettle by an oil pump; the vacuum degree was -0.1Mpa, the heating temperature was 40 ℃, and the impregnation was 4.5 hours;
[0091] S4 cooling and crushing: The impregnated graphite foam plate is removed, cooled and dried, and crushed into a grinder, sieved through 20 mesh to obtain a graphite composite phase change powder for standby;
[0092] S5. Feeding back: 28 parts of the remaining hexadecanoic acid methyl ester in the vacuum heating kettle in step S3 were withdrawn into a heated stirring furnace, and 0.5 parts of modified MWCTNs, 99 parts of the graphite composite phase change powder obtained in step S4, and 6 parts of polyurethane A liquid were added successively; the temperature was maintained at 40 ° C, the speed was 350r / min, and stirred for 3 hours to ensure that the components were evenly mixed;
[0093] S6. At 40°C, mix the mixed liquid in step S5 with 3 parts of polyurethane B liquid to obtain.
[0094] It should be further explained that in the above-mentioned Examples 1-3 and Comparative Examples 1-5, the preparation process of ester-modified MWCTNs includes: adding 1 g of carboxylated carbon nanotubes (MWCNTs-COOH) to 20 mL of N,N-dimethylformamide (DMF), ultrasonically dispersing for 30 min, slowly adding 15 mL of phosphorus trichloride (PCl3), reacting at 70°C for 14 h, vacuum filtering the feed liquid, washing the filter cake with DMF 4 times to remove unreacted PCl3, adding the filter cake to 12 mL of anhydrous glycerol and 0.4 mL of triethylamine (TEA), heating to 50°C, reacting with magnetic stirring for 24 hours, cooling and filtering, washing the filter cake with deionized water 3-5 times, and drying to constant weight.
[0095] Polyurethane liquid A is 2,2-dihydroxymethylbutyric acid (DMBA), α-acetyl-γ-butyrolactone and guanidine carbonate in a mass ratio of 40:19:12, and polyurethane liquid B is a mixed prepolymer of polytetramethylene glycol (PTMG-1000), 4,4'-diisocyanate dicyclomethane (HMDI), isophorone diisocyanate (IPDI) and dibutyltin dilaurate in a mass ratio of 70:24:20:0.03.
[0096] The melting temperature and melting enthalpy of the composite phase change materials prepared in Examples 1-3 and Comparative Examples 1-6 were measured by a DSC214 differential scanning calorimeter, the thermal conductivity was measured by a Hot Disk, and the phase separation state of the materials was observed after 1500 hot and cold cycles.
[0097] Environmental conditions: Temperature: 23±2℃; Humidity: 50±5%RH;
[0098] Test standards: GB / T 19466.1-2004, GB / T 19466.3-2004;
[0099] Test conditions:
[0100] In a N2 environment, the temperature was raised from -40°C to 100°C at a rate of 20°C / min and kept constant for 5 min.
[0101] See Table 1 for details:
[0102] Table 1
[0103] Performance parameter examples Melting temperature(℃) Melting enthalpy (J / g) Thermal conductivity (W / m·K) Phase separation state Example 1 28.3 212.0 5.096 No phase separation Example 2 44.0 202.3 4.986 No phase separation Example 3 65.2 206.0 5.105 No phase separation Comparative Example 1 28.2 180.1 3.965 No phase separation Comparative Example 2 28.4 210.2 5.318 No phase separation Comparative Example 3 28.3 219.2 5.531 Phase separation Comparative Example 4 28.2 205.3 6.120 No phase separation Comparative Example 5 28.4 208.4 3.357 No phase separation
[0104] It can be seen from Examples 1-3 that the present invention regulates the phase change temperature and phase change enthalpy of the system by changing the type of phase change material.
[0105] It can be seen from Example 1 and Comparative Examples 1-3 that the addition of polyurethane effectively alleviates the phase separation of the system. Figure 2 As shown in the figure, polyurethane is a high molecular polymer, and its molecular chain exists in the form of cross-linking, network structure or dispersion, thus forming a spatial obstruction effect, making it more difficult for the graphite / PCM composite particles, high thermal conductive fillers and free paraffin droplets inside the system to move; in addition, the polyurethane and PCM, high thermal conductive filler molecules interact through van der Waals forces, which increases the cohesion of the system, thereby increasing the viscosity of the system and improving the phase separation problem. Figure 3 As shown, phase separation occurred in Comparative Example 3 after 1500 hot and cold cycles, which also confirms the above statement.
[0106] In the composite system, the connection points of the temporary network structure formed by polyurethane are in a process of continuous destruction and re-formation, so the composite system retains a certain fluidity. At the same time, the rheological properties of the system are controlled by the end groups, among which the long end groups have a strong effect, ensuring effective thickening, and their exchange rate is slow, showing pseudoplasticity; while the exchange rate of short end groups is fast. By changing the ratio of polyurethane AB liquid to adjust the length ratio of the end groups, the fluidity and softness of the composite phase change material can be adjusted within a certain range.
[0107] It can be seen from Example 1 and Comparative Examples 4-5 that the addition of high thermal conductivity fillers has a significant effect on the thermal conductivity of the system: the thermal conductivity of the system increases with the increase in the proportion of high thermal conductivity fillers. This is because the modified MWCTNs build a heat transfer bridge for the dispersed graphite / PCM particles in the PCM-polyurethane system, reducing the interfacial thermal resistance between polyurethane-PCM-graphite / PCM, and increasing the thermal conductivity of the composite system to more than 15 times that of pure PCM.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A high performance and high thermal conductivity composite phase change material, characterized in that: The invention comprises the following materials in parts by weight: 5-50 parts of PCM, 70-150 parts of foamed graphite composite PCM particles, 0.01-1 parts of nucleating agent, 1-5 parts of high thermal conductivity filler and 5-30 parts of polyurethane; the foamed graphite composite PCM particles comprise 1-10 parts of foamed graphite and 10-140 parts of PCM; the high thermal conductivity filler is esterified multi-walled carbon nanotubes.
2. A high performance and high thermal conductivity composite phase change material according to claim 1, characterized in that: The polyurethane is a polyether polyurethane gel with a Shore C hardness of 0-50 Shore C hardness.
3. The high performance and high thermal conductivity composite phase change material according to claim 1, characterized in that: The PCM includes fatty acid esters such as methyl hexadecanoate, methyl octadecanoate, ethylene glycol distearate, and one or more of 1-dodecanol and 1-tetradecanol.
4. A high performance and high thermal conductivity composite phase change material according to claim 2, characterized in that: The carbon content of the foamed graphite is 99%, and its density includes any value between 0.03 and 0.3 g / cm³.
5. The high performance and high thermal conductivity composite phase change material according to claim 1, characterized in that: The nucleating agent includes one or more of TiO2, ZnO, Al2O3, SiC, and AgI.
6. A process for preparing a high performance and high thermal conductivity composite phase change material according to any one of claims 1 to 5, characterized in that the steps include: S1. Preheating and melting: Heat the PCM raw material to 50~150℃ to ensure full melting; S2. Adding nucleating agent: When the temperature drops to 40-80°C, add the nucleating agent and stir at a speed of 350-500 r / min for 1-2 hours to ensure that the nucleating agent is evenly distributed in the liquid PCM to obtain a liquid feed; S3. Vacuum impregnation: The foamed graphite sheet is mixed with the liquid, and the vacuum degree is -0.1Mpa, the heating temperature is 40~80 ℃, and the impregnation is 3~15 hours; S4 cooling and crushing: The impregnated foam graphite plate is removed, cooled and dried, crushed, 10 to 40 mesh sieved to obtain a graphite composite phase change powder; S5. Retracting and adding: Adding the high thermal conductivity filler, the graphite composite phase change powder obtained in step S4, and the polyurethane A liquid to the remaining portion of the liquid in step S3, maintaining the temperature at 40~80°C, the speed at 350~500r / min, stirring for 2~3 hours to ensure that the components are evenly mixed; S6. At 40-80° C., mix the mixed material in step S5 with the polyurethane B liquid to obtain a high-performance and high-thermal-conductivity graphite composite phase change material.
7. The preparation process of the high performance and high thermal conductivity composite phase change material according to claim 6, characterized in that: The polyurethane liquid A comprises 2,2-dihydroxymethylbutyric acid, α-acetyl-γ-butyrolactone and guanidine carbonate, and the polyurethane liquid B comprises a mixed prepolymer of polytetramethylene glycol, 4,4'-diisocyanate dicyclomethane, isophorone diisocyanate and dibutyltin dilaurate.
8. Use of the high performance and high thermal conductivity composite phase change material according to any one of claims 1 to 5 in phase change energy storage materials.
Citation Information
Patent Citations
Phase change gel for sunlight photo-thermal conversion, and preparation method thereof
CN113621349A
Flexible heat-conducting phase-change gel material and preparation method and application thereof
CN113652204A
Composite phase change material, phase change gel and preparation method and application thereof
CN115612462A
High-effect composite polyurethane phase change material and preparation method thereof
CN108424503A